Molecular insights of fungal endophyte co-inoculation with Trichoderma viride for the augmentation of forskolin biosynthesis in Coleus forskohlii - Mastan, Anthati; Rane, Digeshwar; Dastager, Syed G.; Babu, C. S. Vivek (Phytochemistry, 2021)
To understand the compatibility of three native endophytic fungi Phialemoniopsis cornearis (SF1), Macrophomina pseudophaseolina (SF2) and Fusarium redolens (RF1) with Trichoderma viride (TV1) on Coleus forskohlii in enhancing plant growth and forskolin content, field experiments were conducted. Co-inoculation of RF1+TV1 showed significant improvement in plant growth (52%), root biomass (67%), and in planter forskolin content (94%), followed by treatment with SF2+TV1 and SF1+TV1. qRT-PCR was carried out to quantify expression of five key forskolin biosynthetic pathway genes (CfTPS2, CfTPS3, CfTPS4, CfCYP76AH15, and CfACT1-8) in RF1+TV1 treated C. forskohlii plants. Elevated expression of CfTPS2, CfTPS4, CfCYP76AH15 and CfACT1-8 genes was observed with RF1+TV1 combination as compared to uninoculated C. forskohlii plants. Besides, RF1+TV1 treatment considerably reduced the severity of nematode infection of C. forskohlii plants under field conditions. Thus, congruent properties of F. redolens (RF1) were witnessed with co-inoculation of T. viride (TV1) under field conditions which resulted in enhanced forskolin content, root biomass, and reduced nematode infections in C. forskohlii. Overall, this approach could be an economical and sustainable step towards cultivation of commercially important medicinal plants.
Keywords: Co-inoculation; Coleus forskohlii; endophytes; Forskolin; Lamiaceae; Trichoderma viride

Insights on biorational potential of Ocimum gratissimum essential oil and its binary combination with monoterpene phenol for control of rice weevil (Sitophilus oryzae) and aflatoxigenic fungi. - Remesh, V. Archana; Raveendran, Ashika; Bincy, K.; Wagh, Vasudev S.; Dastager, Syed G.; Babu, C. S. Vivek (Food Bioscience, 2022)
Food grain storage is a difficult task due to insect infestation and subsequent mycotoxin contaminations which adversely affects the nutritional quality of grains and leading to economic loss. Current research focuses on contact and fumigant toxicity effects of essential oils (EO) and aroma compounds against Sitophilus oryzae and growth inhibition of aflatoxigenic fungi. The EO of Ocimum gratissimum comprised of thymol (46.8%), gamma-terpi-nene (14.04%) along with o-cymene (11.76%). Also, Cymbopogon flexuosus rich in citral (76.3%) and geraniol (84.6%) and Cymbopogon nardus having geraniol (49.24%) and geranyl acetate (20.9%) were all evaluated using a dose of 25 mu L (Conc-833.3 mu L/L air) against S. oryzae. All the compounds showed significant mortality (>95%) at 24 h of exposure. The insecticidal property of O. gratissimum oil chemotype showed a strong contact and fumigant toxicity against S. oryzae at a highest dose of 25 mu L (Conc-833.3 mu L/L air) within 24 h. It has been further evaluated on three aflatoxigenic fungal strains which showed reduction in growth and aflatoxin content (Aflatoxin B and G), which was markedly reduced upon the treatment. The binary mixture interaction of O. gratissimum oil with monoterpene phenol (carvacrol) was assessed and the specific binary mixture of 80:20 ratio (having additive property) acts as a contact insecticide with 100% mortality. Hence, essential oil of less explored Ocimum species (O. gratissimum) and its binary mixture could be deployed as potential biorational for control of rice weevil (Sitophilus oryzae) and aflatoxigenic Aspergillus spp.
Keywords: Aflatoxigenic fungi; Binary combination; Essential oil; Ocimum gratissimum; Sitophilus oryzae